The male terminalia of some African species of Helina Robineau-Desvoidy, 1830 (Diptera, Muscidae) - Couri, Márcia S.; Pont, Adrian C. (Zootaxa, 2018)
The morphology of the male terminalia of fourteen African species of Helina Robineau-Desvoidy, 1830 (Diptera, Muscidae) is described and illustrated: H. dorsalis (Stein, 1914); H. emdeni Pont, 1980, H. fuscibasis Emden, 1951; H. gracilior Emden, 1951; H. hirtipes metatarsalis Emden, 1951, H. juxtamedialis Emden, 1951; H. lasiopa Emden, 1951; H. mollis (Stein, 1906); H. naivashensis Emden, 1951, stat. nov. (herein raised to species rank); H. nemoralis (Stein, 1913); H. novarae (Schiner, 1868), H. penicillata Emden, 1951; H. quadruplex (Stein, 1913); and H. trinubilifera (Malloch, 1921). These species demonstrate that the terminalia can be very varied, with different shapes of sternite 5, sometimes with very strong and long setae, and a short or elongated cercal plate and surstylus that sometimes can bear spines. Some of these species also share other external characters that are unusual among Helina, such as the arrangement of the katepisternal setae as an equilateral triangle, the absence of an anterodorsal seta on mid tibia, and wings with dark clouds. Most of these species are well described in the literature, but the male terminalia have never been studied in detail. The material studied here is deposited in the Natural History Museum (BMNH), London, United Kingdom.